HPB P60 Pancreatic Carcinosarcoma as a rare cause of upper gastrointestinal bleeding requiring resection. (7th December 2022) - King, Emily; Elmasry, Mohamed; Hughes, Daniel; Urbonas, Tomas; Gordon-Weeks, Alex; Silva, Michael; Reddy, Srikanth; Soonawalla, Zahir; Udupa, Venkatesha
Abstract: Background: Pancreatic carcinosarcoma is a rare malignant neoplasm and has a very poor prognosis. Diagnosis is mainly by pathological examination including immunohistochemistry (IHC) of the biopsy or resected specimen. Due to the rarity of the cancer, information regarding clinical presentation, pathology and management is limit to a few case reports. Methods: We report a 61-year-old fit and healthy male, who presented to the emergency department with melaena and syncope. Initial CT scan showed a pancreatic body/tail tumour, likely pancreatic cancer without nodal or intra-abdominal metastasis. Upper GI endoscopy revealed a lesion in the second part of the duodenum, with a visible vessel, and evidence of recent bleeding . Two clips were applied, and a biopsy of the lesion showed ulcer slough only. Tumour markers and IgG4 levels were normal. An MRI pancreas showed no definite pancreatic mass, features of chronic pancreatitis and irregular bile ducts. HPB MDT consensus was to proceed for EUS, which confirmed a hypoechoic, vascular, 3cm mass lesion in D1-D2. Biopsies again, showed ulcer slough. A PET CT scan showed avidity in the second part of the duodenum and pancreatic head, neck and distal body. The patient presented to the surgical emergency unit twice during this time with symptoms of anaemia requiring IV iron and blood transfusions, and with early signs of obstruction, which settled with conservative management. Interval MRI showed increase in size of the duodenal mass, and stable appearance of the lesion in the head of the pancreas. Eventually, semi-emergency total pancreaticoduodenectomy and splenectomy was undertaken. Results: Intraoperatively, a large D2 tumour was found extending into the pancreatic head posteriorly, compressing but not infiltrating the IVC. The rest of the pancreas was hard in consistency and nodular. Soft lymph nodes were found at the aorto-caval, common hepatic and around the SMA. There was no obvious intra-abdominal metastasis. The final histopathology showed a malignant, biphasic tumour favouring pancreatic carcinosarcoma staged pT3 N0 (0/29) L1 V1 R1 (posterior and SMV). On molecular cytogenetic analysis there was no evidence of rearrangement associated with synovial sarcoma in the cells examined. He recovered well post operatively and has commenced adjuvant chemotherapy of modified Folfirinox. Conclusions: Pancreatic carcinosarcoma is a rare entity, which due to its unusual presentation, can be challenging to manage. Prompt MDT discussion is instrumental in such cases. The assessment of different radiological modalities, showing progressive increase in the size of the lesion within a short time period, raised the suspicion of an aggressive mitotic lesion, with the repeat biopsies unlikely to yield diagnosis in an otherwise operable lesion. Ultimately, the patient underwent a semi-emergency, total pancreaticoduodenectomy and splenectomy due to ongoing bleeding and the rapidly growing tumour size. In this case, surgery followed by adjuvant chemotherapy has been adopted as the optimum management strategy, for both bleeding control, and oncological benefit.